The Historical Background of the State Liability without Fault Principle in French Administrative Law - Kerdlapphon, Kristhyada (STOU Academic Journal of Research and Innovation (Humanities and Social Science), 2024)
The principle of liability without fault in France is developed to determine that the state or government is liable to individuals who have suffered damages due to the state or government’s performance of its duties, even if the government's actions were legal and without any faults. The Historical background of the state liability without fault principle in France is based on the theory of exceptional risks and the theory of equality of citizens in bearing exceptional burdens for the public benefit. The Council of State, as the highest administrative court, has developed the principle of liability without fault in many cases where specific laws do not directly specify. In judging the cases, the Council of State has applied the principle of liability without fault as a general principle of law, based on the perception of preventing damages without compensation. Many countries worldwide have also adopted the French model of liability without fault to explain and justify state liability without fault in their own countries as well.